John Marchmont's Legacy, Volume 2 (of 3) - Braddon, M. E. (Mary Elizabeth), 1835-1915 (Salt Lake City, UT : Project Gutenberg, 2010)
"John Marchmont's Legacy, Volume 2 (of 3)" by M. E. Braddon is a novel written in the mid-19th century. The story continues to unfold in the context of romance and personal conflict, exploring themes of love, jealousy, and social dynamics among characters centered around the heiress Mary Marchmont. Key players include Edward Arundel, who is determined to protect Mary from her manipulative stepmother, Olivia, amidst emotional turmoil and misunderstandings. At the start of this volume, the narrative picks up with Edward discovering that Mary has left after a tumultuous event at the Marchmont Towers. A letter reveals her deep insecurities and feelings of unworthiness, prompting Edward's urgent desire to find her. As the plot thickens, Edward's fierce determination emerges as he confronts Olivia's role in Mary's distress. The opening conveys a brooding atmosphere filled with tension as Edward races against time to rescue Mary, showcasing his unwavering affection and foreshadowing the potential complexities of their future together. (This is an automatically generated summary.)
Release date is 2010-12-01
Produced by Clare Graham, using scans from the Internet Archive
Keywords: Triangles (Interpersonal relations) -- Fiction; Children of clergy -- Fiction; Lincolnshire (England) -- Fiction; Women intellectuals -- Fiction